Molecular dominance investigation of large‐sized Chinese mitten crab (Eriocheir sinensis) parents based on the male accessory gland transcriptome. (7th March 2021) - Xuan, Fujun; Fu, Longlong; Zhao, Xinyue; Hua, Zonglin; Cao, Jiaxin; Zhang, Jianguang; Pan, Jianlin; Tang, Boping; Guan, Weibing; Cheng, Yongxu
Abstract: Germplasm degradation is one of the important issues for the healthy development of Chinese mitten crab ( Eriocheir sinensis ) industry. Nowadays, many farming practices have evidenced the seedling superiority of large‐sized parents (≥200 g male, ≥150 g female), but the underlying molecular mechanisms remain unclear. This study investigated the advantage of large‐sized male parents in E .  sinensis breeding at the molecular level. Accessory glands were obtained from three large‐sized male crabs and three medium‐sized male crabs for transcriptome sequencing. A total of 8000 differentially expressed genes (DEGs, 2773 up‐regulated and 5227 down‐regulated) were identified between the large‐ and medium‐sized groups. According to previous studies, 324 genes involved in 12 reproductive, immune response and growth pathways were identified. A total of 38 common genes were selected, and 11 were verified to have consistent expression trends in the sequencing data after quantitative real‐time PCR validation. These validated genes, such as TRINITY_DN1908_c0_g2, TRINITY_DN1908_c1_g1, TRINITY_DN19325_c0_g1, TRINITY_DN2026_c1_g1, TRINITY_DN70348_c1_g1, TRINITY_DN15892_c0_g3 and TRINITY_DN891_c0_g5, were significantly enriched in the phagosome, insulin secretion and apoptosis pathways. Through comparative analysis, our study elucidated for the first time based on a male accessory gland transcriptome that using large‐sized male E .  sinensis as broodstock may have advantages for growth, reproduction and immune response. In addition, the phagosome, insulin secretion and apoptosis pathways may be closely related to the advantage of large‐sized male mitten crabs. These validated genes may be key biomarkers of large‐sized male mitten crabs.